Peningkatan Hasil Belajar Tematik Terpadu dengan Model Problem Based Learning di Sekolah Dasar - Reinita, Reinita (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
In accordance with the 2013 curriculum, Elementary Schools use thematic learning approach, which means that all subjects are integrated into certain themes, including Pancasila and Citizenship Education (PPKn). In order to achieve learning objectives, various forms of learning models are used. This article aims to describe the improvement of learning outcomes using Problem Based Learning (PBL) model in integrated thematic learning particularly on diversity and energy saving materials for fourth grade students of SDN 06 Batu Taba, Agam regency, West Sumatra province. The research subjects were teachers and 27 students. The type of research was classroom action. The results showed an increase in the Learning Implementation Plan (RPP). In the first cycle, the average predicate was good, then increased to be very good in the second cycle. The implementation of teacher activities in cycle I obtained an average of sufficient predicate, and increased in cycle II to be very good. The implementation of the activities of the students in the first cycle obtained sufficient average predicate and increased in the second cycle to be very good. Student learning outcomes in the first cycle obtained sufficient average predicate and increased in the second cycle to be very good. Therefore, it can be concluded that the PBL model can improve student learning outcomes in integrated thematic learning in elementary schools. Keywords: problem based learning model, learning outcomes, integrated thematic, classroom action research, learning implementation plan ABSTRAK Sesuai dengan kurikulum 2013, Sekolah Dasar menggunakan pendekatan pembelajaran tematik, yaitu semua mata pelajaran terintegrasi ke dalam tema-tema tertentu, termasuk Pendidikan Pancasila dan Kewarganegaraan (PPKn). Untuk mencapai tujuan pembelajaran, sekolah menggunakan berbagai bentuk model pembelajaran. Artikel ini bertujuan untuk mendeskripsikan peningkatan hasil belajar dengan menggunakan model Problem Based Learning (PBL) pada pembelajaran tematik terpadu terutama materi keberagaman dan hemat energi bagi siswa kelas IV SDN 06 Batu Taba, Kabupaten Agam, Sumatera Barat. Subjek penelitian adalah guru dan 27 orang peserta didik. Jenis penelitian adalah tindakan kelas. Hasil penelitian menunjukkan adanya peningkatan pada Rencana Pelaksanaan Pembelajaran (RPP). Pada siklus I, diperoleh rata-rata predikat baik, kemudian meningkat pada siklus II menjadi sangat baik. Pelaksanaan aktivitas guru di siklus I memperoleh rata-rata dengan predikat cukup, dan meningkat pada siklus II menjadi sangat baik. Pelaksanaan aktivitas siswa pada siklus I memperoleh rata-rata dengan predikat cukup dan meningkat pada siklus II menjadi sangat baik. Hasil belajar siswa pada siklus I memperoleh rata-rata predikat cukup dan meningkat pada siklus II menjadi sangat baik. Dengan demikian, dapat disimpulkan bahwa model PBL dapat meningkatkan hasil belajar siswa pada pembelajaran tematik terpadu di Sekolah Dasar. Kata kunci: model Problem Based Learning (PBL), hasil belajar, tematik terpadu, penelitian tindakan kelas, Rencana Pelaksanaan Pembelajaran